Differential Effect of Cyclooxygenases 1 and 2 in Late Reproductive Age Women - Israa Burhan Raoof; Muthanna I. Al-Ezzi (College of Pharmacy / Mustansiriyah University, 2019)
Cyclooxygenases enzymes (COX) are related with ovulation, apoptosis and menstrual disorder. Several studies demonstrate that COX 1 is one of the major sources of prostaglandin but COX 2 is more important in the late reproductive age women. Prostaglandin is bioactive compound excreted from Arachidonic   acid by Cox 1 and Cox 2, play role in the fertility and ovulation but when increased above the normal level especially in menstrual cycle, ectopic pregnancy is attributed to this cause. Cox 1 and Cox 2 inhibitors have been regulated the inflammatory responses include cytokines and tumor growth factors which produced from neutrophil cells by cyclooxygenases activation, it has been used to regular prostaglandin action, especially PGG2 and PGH2. Any changes in the endometrial cells lead to increased vascular inflammation that developed to the late reproductive disease. Steroidogenesis characterized by increased levels of estrogen in the uterus caused uterine infections and elevated cyclooxygenases levels especially during uterine contractions process.